Fundos de titularização de crédito em Portugal: perspectiva do emitente e investidor - Marcos, Joana Filipa da Cruz (2012)
Asset securitization has become a key element in raising funds in both foreign and domestic capital markets. It emerged in the seventies in the U.S.A. and in Europe, and in the recent years we have seen a significant increase in volume and value of emissions of assets securitization. The goal of this work is to study the underlying reasons for this outstanding evolution, as well as to clarify the concept of asset securitization, to describe the process of financing operations and describe the evolution of this product in the Portuguese market. We analyze the case se of an issuance of Residential Mortgage Back Securities by a large Portuguese bank, in which we will focus on the roll out of the operation and its market performance. After the subprime crises, the demand for this product has fall, prices have decreased and yields have increased, providing a good return for the level of rating. Asset securitization is considered as a means of alternative financing, has proved to be a very useful tool which allows reconciling the goals and needs of investors, issuers and market.